Implementasi Metode Certainty Faktor Untuk Rekomendasi Pembelian Hp - Komang Arsa Wiguna; I Gede Arta Wibawa (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
In this study, the implementation of the Certainty Factor (CF) method was carried out to provide consumers with more accurate cell phone purchase recommendations. This method combines expert knowledge and user data to produce more reliable recommendations. The implementation process involves collecting relevant HP feature data, establishing rules based on expert knowledge, calculating confidence factors (CF) based on the level of expert confidence and suitability of user data, and merging the CFs of all rules to produce a final recommendation. Through testing and evaluation, the Certainty Factor method is proven to be able to provide accurate HP purchase recommendations and assist consumers in choosing a HP that suits their preferences and needs. However, this research still requires further development to improve the accuracy of recommendations and to conduct tests with larger and more diverse datasets to ensure the effectiveness and validity of this method in the context of H purchase recommendations.